Changes in soil temperature and water content under mobile soil steam disinfection - Yang, Zhenjie; Wang, Xiaochan; Ameen, Muhammad (International Journal of Agricultural and Biological Engineering, 2021)
The soil steam injection method is one of the most effective disinfection methods, and the determination of the steam pipe structure parameters is very important. The steam capillary diameter (SCD) affects the steam flow field in each pipe, which in turn affects the steam changes in the soil flow range and soil temperature (ST). Larger SCD would make lower ST in clay loam, silt loam, and sandy clay loam. The effectiveness of an SCD of 10 mm was verified by a mobile disinfection test at walking speeds of 10 cm/min and 30 cm/min under soil water content (SWC) of 15% and 35%, respectively. The results showed that when the walking speed was 10 cm/min, the initial SWC was proportional to the ST. However, when the walking speed was 30 cm/min, the law was exactly the opposite; that is, the initial water content is inversely proportional to the ST. The research can provide a theoretical research foundation for increasing soil temperature for efficient soil steam disinfection.Keywords: soil steam disinfection, steam capillary diameter, steam capillary vent, soil temperature, soil water contentDOI: 10.25165/j.ijabe.20211403.5026Citation: Yang Z J, Wang X C, Ameen M. Changes in soil temperature and water content under mobile soil steam disinfection. Int J Agric & Biol Eng, 2021; 14(3): 140–147.